Lesson Study & Project Based Learning sebagai Upaya Membentuk Forum Diskusi dan Perbaikan Kualitas Pembelajaran Guru IPA - Saleh Hidayat; Erie Agusta; Rusdy Abdullah Siroj; Yetty Hastiana (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
The implementation basic of this dedication begun by the problem of having not a forum for science teacher at SMPN 3 Banyuasin 1 to discuss in solving the problems faced at class. This dedication activity was aimed 1) to increase science teachers’ knowledge at SMPN 3 Banyuasin 1 about lesson study with project based learning model (PjBL) and 2) to know the level of participant's satisfaction toward the implementation of dedication activity. Implementation Methods of dedication activity included: 1) socialization of the PjBL model; 2) socialization of lesson study; 3) socialization of learning devices types; and 4) assistance of implementation simulation of lesson study based PjBL consisting of plan, do, and see. Data collection of knowledge was done by using the questions given before and after the PkM activity, while the satisfaction level of dedication implementation of devotion was taken by using the questionnaire. Data analysis of knowledge and questionnaire using descriptive analysis. The results of the dedication showed that 1) there was the increase of  Science Teachers’ knowledge of SMPN 3 Banyuasin 1 about lesson study with PjBL model from 66 to 74,6; and 2) there was the indication of the participants being very satisfied of the implementation of dedication activities.